Assessment of availability, value, and challenges of references service in academic libraries of universities of North West geo-political zone in Northern Nigeria - Ahmed, Aliyu (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2017)
The study examines reference services in academic libraries in the Northwest geopolitical zone in Nigeria. The study used a sample of 162 staff in the reference section in three academic libraries that comprise of Ahmadu Bello University (ABU), Bayero University Kano (BUK) and Usmanu Danfodio University, Sokoto (UDUS) that were drawn through Stratified Random Sampling technique. Questionnaire instrument was used in generating the data. The research objectives are to identify the environment of reference services, value and challenges in universities libraries in Northwest zone, Nigeria. The findings of the study show that there is availability of reference services in academic libraries in the Northwest zone, student valued materials located in the reference section and large number of students is one of the challenges of reference sections in academic libraries. The study concludes that reference services are readily available and functional. It is recommended that capacity to accommodate more students should be increased and quality of service be maintained and improved.